Sociodemographics and Dietary Intake Associations with Gestational Weight Gain Rates Among Gestational Diabetes Mellitus Mothers - Abdul Hamid, Syahrul Bariah; Nazari, Muhammad Hazeem Na’immullah Mohammad; Mohd Asri, Anis Haneesa; Shuhaimi, Farhanah (Jurnal Gizi dan Pangan, 2024)
This study aims to assess the rates of Gestational Weight Gain (GWG) among pregnant mothers with and without Gestational Diabetes Mellitus (GDM) and to investigate the sociodemographic and dietary intake factors associated with the rates of GWG. This cross-sectional study involved 77 pregnant mothers visiting selected government clinics. Sociodemographics, medical records, and dietary intake were obtained through a self-administered questionnaire. The mean age of the participants was 30.48±5.0 years old with 48.1% (n=37) of them were GDM diagnosed. Moreover, 27 (73.0%) of GDM mothers experienced abnormal GWG. Their mean intakes were 1,481±389 kcal/day, macronutrients such as carbohydrate, protein, and fat were 199.9±59.3 g/day, 75.5±23.9 g/day, 44.1±15.3 g/day accordingly, fiber was 6.9±7.0 g/day and followed by micronutrients such as folate, calcium, iron, and zinc were 137.4±78.9 μg/day, 738.6±335.3 mg/day, 16.8±7.1 mg/day, and 6.0±2.6 mg/day respectively. This study reported no significant association between GDM status and GWG rates but there was a significant association between pre-pregnancy BMI and zinc intake with rates of GWG among pregnant mothers (p<0.05). In conclusion, the latest guidelines of GWG rates should include GDM status among pregnant mothers according to the specific pre-pregnancy Body Mass Index (BMI) to ensure, they can adhere to the new recommendations and lower the risk of pregnancy complications that may occur due to abnormal rates of GWG.